ANALISIS LITERASI MATEMATIS SISWA KELAS VIII DIKAJI BERDASARKAN KONTEN UNCERTAINTY AND DATA - Anjani, Ayu; Halini, Halini; Astuti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThe goal of this research to describe the mathematical literacy of student in grade VIII studied based on uncertainty and data content at SMP Negeri 03 Pontianak. The method we used in this research is descriptive in a study case form. The subjects chosen in this research were students of grade VIII A as many as 35 people. The results of the test we did shown that the attainment of student’s mathematical literacy is mostly in Level 1 until Level 4, Level 1 can be attained by 85.71% of students, Level 2 by 100% of students, Level 3 by 80% of students, and Level 4 by 97.14% of students. Meanwhile,few studentcan attain level 5about 8.57%of students. The last,there is no students can attain level 6.Factors considered as the cause of the low level of attainmentin level 5 and Level 6 is student not able to interpret the data available and relate some data to information from other sourcesnor reasoning and communicating ideas.          Keywords: Achievement, Literasi Matematis, Uncertainty and Data